Effectiveness Of Outdoor Learning Optimization Program In Learning Social Studies - Prasetya, Sukma Perdana; Segara, Nuansa Bayu; Imron, Ali (JPI (Jurnal Pendidikan Indonesia), 2020)
Outdoor learning is potential to expose social and natural phenomena related to social studies. However, the social studies teachers seldom to practice outdoor learning on certain occasions. This article has two aims. First, interpreting social studies teacher perspective about the simulation of an outdoor learning laboratory. Second, explain the teacher's obstacle if they are practicing outdoor learning in the school. Step of the research consist of 1) in service-learning 1; 2) on the job learning; 3) in service-learning 2. The participants of this study involved 20 secondary high school active teachers of social studies in Surabaya. The data collecting technique used in this study is a questioner to measuring teacher's perspectives about the outdoor learning simulation in Surabaya, Sidoarjo, Mojokerto, Jombang,Tuban. Then, interview guidelines were used to perceive the data about teacher's obstacles to practice outdoor learning programs. The data analysis technique for examined teachers' perspectives is the percentage and discriminant statistics. The result of this study confirms that learning outdoor program offers a positive outcome. That is, 1) integrity while the social studies learning, extending social studies content, and helpful for difficult content; 2, Motivation improvement, attention and provide the student concrete experience; 3) Social studies learning to be fun, effective, and contextual. However, Social studies teachers assume laboratory outdoor activity is not efficient and hard to do, because they need a big fee, lengthy time, and require teachers' field experience for dominating social studies content